Percutaneous lumbar annular puncture: A rat model to study intervertebral disc degeneration and pain‐related behavior - Richard A. Wawrose; Brandon K. Couch; Malcom Dombrowski; Stephen R. Chen; Anthony Oyekan; Qing Dong; Dong Wang; Chaoming Zhou; Joseph Chen; Karthik Modali; Marit Johnson; Zachary Sedor‐Schiffhauer; et al. (JOR Spine, 2022)
Abstract Background Previous animal models of intervertebral disc degeneration (IDD) rely on open surgical approaches, which confound the degenerative response and pain behaviors due to injury to surrounding tissues during the surgical approach. To overcome these challenges, we developed a minimally invasive percutaneous puncture procedure to induce IDD in a rat model. Methods Ten Fischer 344 male rats underwent percutaneous annular puncture of lumbar intervertebral discs (IVDs) at L2‐3, L3‐4, and L4‐5. Ten unpunctured rats were used as controls. Magnetic resonance imagings (MRIs), serum biomarkers, and behavioral tests were performed at baseline and 6, 12, and 18 weeks post puncture. Rats were sacrificed at 18 weeks and disc histology, immunohistochemistry, and glycosaminoglycan (GAG) assays were performed. Results Punctured IVDs exhibited significant reductions in MRI signal intensity and disc volume. Disc histology, immunohistochemistry, and GAG assay results were consistent with features of IDD. IVD‐punctured rats demonstrated significant changes in pain‐related behaviors, including total distance moved, twitching frequency, and rearing duration. Conclusions This is the first reported study of the successful establishment of a reproducible rodent model of a percutaneous lumbar annular puncture resulting in discogenic pain. This model will be useful to test therapeutics and elucidate the basic mechanisms of IDD and discogenic pain.